Efficient sorption and photocatalytic degradation of malachite green dye onto NiS nanoparticles prepared using novel green approach - Prasad, Kumar Suranjit; Prajapati, Sheel; Selvaraj, Kaliaperumal (Korean Journal of Chemical Engineering, 2015)
The extract of the Asparagus racemosus leaf tissue works as a stabilizing and capping agent and assists the formation of stable colloidal nanoparticles. Nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX and XRD, respectively. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of near spherical, polydispersed, crystalline NiS of diameter ranging from 4-27 nm. X-ray diffraction studies showed the formation of 110, 101, 300, 021, 220, 221, 131, 410, 401, 321, 330 and 021 planes of hexagonal NiS. EDAX analysis confirmed the presence of Ni and S in nanosphere. The maximum sorption capacity (q (m) ) of NiS nanoparticles for MG dye was found to be 64.85 mg/g. Decolorization as well as disintegration of malachite green under white light illumination was confirmed by LC-MS studies. Results of the present study suggest that nanosized NiS can play an instrumental role in photocatalytic degradation of malachite green dye present in water bodies.
Keywords: Degradation; FTIR; Malachite Green; NiS Nanoparticles; TEM

Microbial selenium nanoparticles (SeNPs) and their application as a sensitive hydrogen peroxide biosensor - Prasad, Kumar Suranjit; Vaghasiya, Jayraj V.; Soni, Saurabh S.; Patel, Jitesh; Patel, Rinkesh; Kumari, Madhu; Jasmani, Falguni; Selvaraj, Kaliaperumal (Applied Biochemistry and Biotechnology, 2015)
The cell-free extract, a crude enzyme (cytosolic and membrane fraction) obtained from an environmental isolate, Bacillus pumilus sp. BAB-3706 worked as excellent in reducing as well as stabilizing agent and facilitated the formation of stable colloidal selenium nanoparticles (SeNPs). Resulting nanoparticles were characterized using UV-vis spectrophotometer, TEM, EDAX, FT-IR and XRD, respectively. A working electrode was modified by coating the surface of indium tin oxide (ITO) with colloidal SeNPs. Successive additions of H2O2 (100 to 600 mu M) in conventional three electrodes system, cyclic voltammeter with potential scan rate 25.0 mV/s, in 0.1 M phosphate buffer solution (PBS) yielded increase in current. A perpetual amperometric response at fixed potential (-1.0 V) and at selected time interval of 100 s showed different magnitude of current at every addition of H2O2. The linear range of detection of H2O2 was from 5 to 600 mM (R (2) = 0.9965), while the calculated limit of detection was found to be 3.00 mu M. The current study suggested that microbial SeNPs can be used for fabrication of low cost, sensitive H2O2 biosensor.
Keywords: Biosensor; EDAX; Hydrogen peroxide; Selenium nanoparticles; TEM; UV-vis spectroscopy